PENINGKATAN KEMAMPUAN BERHITUNG AWAL ANAK USIA 5-6 TAHUN MELALUI PERMAINAN CAK INGKING GERPAK DIPAUD ATHAYA NAFFA'KOTA PALEMBANG - I Desak Gede Agung M.H; Taruni Suningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve early numeracy skills of children aged 5–6 years through the Cak Ingkling Gerpak traditional game at PAUD Athaya Naffa’, Palembang. The research employed Classroom Action Research (CAR) based on the Kemmis dan McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 15 children in Group B. Data were collected through observation and documentation using an observation checklist based on six early numeracy indicators. Data were analyzed qualitatively and quantitatively using percentage analysis. The findings showed a significant improvement in children’s numeracy skills, increasing from 13.33% in the pre-cycle to 46.67% in Cycle I and reaching 86.67% in Cycle II, exceeding the predetermined success indicator. The Cak Ingkling Gerpak game effectively enhanced children’s understanding of number concepts, symbol–quantity matching, and simple addition through concrete and enjoyable play-based learning.